2011
DOI: 10.1123/jsr.20.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Ability, Motor Coordination, and Functional Determinants After Anterior Cruciate Ligament Reconstruction

Abstract: Although muscle strength and functional performance clearly increased from the 6th to the 12th mo after surgery, coordination characteristics of involved side remained low. This pattern demonstrated that motor-coordination progression was not affected by strength development. Patients continued to have significant motor-coordination deficits even 12 mo postsurgery. Therefore, the authors recommend that neuromuscular-coordination exercises be included in long-term rehabilitation programs to improve motor coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 26 publications
2
25
0
5
Order By: Relevance
“…Seven were classified as good,43 45–47 53 55 66 26 as fair3 5–9 21 23 37–39 41 42 44 48–50 52 54 56 60–67 and 6 as poor 29 40 51 57–59. Thirty studies did not include all important adverse events that could have an effect on the intervention reported (criterion 8),5–7 9 21 23 29 38–40 42–52 54 56 57 59 60 63 64–67 23 studies did not adequately describe the source population and how they were recruited (criterion 11 and 12),3 5 6 8 21 37–40 42 44 48–52 54 57–60 64 65 24 studies did not describe if the source population was recruited in the same time period (criterion 22),3 8 9 23 29 37–42 44 48–52 54–58 63 64 66 and 29 studies did not report sample size calculation (criterion 27) 3 6–8 21 23 29 38–44 49–53 56–61 63–67. Other criterion, such as criterion 22 and 23, were not commonly fulfilled due to most studies not being randomised, while criterion 14 and 15 were not commonly reported due to lack of blinding.…”
Section: Resultsmentioning
confidence: 99%
“…Seven were classified as good,43 45–47 53 55 66 26 as fair3 5–9 21 23 37–39 41 42 44 48–50 52 54 56 60–67 and 6 as poor 29 40 51 57–59. Thirty studies did not include all important adverse events that could have an effect on the intervention reported (criterion 8),5–7 9 21 23 29 38–40 42–52 54 56 57 59 60 63 64–67 23 studies did not adequately describe the source population and how they were recruited (criterion 11 and 12),3 5 6 8 21 37–40 42 44 48–52 54 57–60 64 65 24 studies did not describe if the source population was recruited in the same time period (criterion 22),3 8 9 23 29 37–42 44 48–52 54–58 63 64 66 and 29 studies did not report sample size calculation (criterion 27) 3 6–8 21 23 29 38–44 49–53 56–61 63–67. Other criterion, such as criterion 22 and 23, were not commonly fulfilled due to most studies not being randomised, while criterion 14 and 15 were not commonly reported due to lack of blinding.…”
Section: Resultsmentioning
confidence: 99%
“…However, in higher level functional tasks that require more coordination and neuromuscular control, similar adaptations are not consistently identified during this same period. 40 Thus, assessment criteria focused on isolated strength measures that do not include motor coordination and power development may be inadequate to identify persistent deficits that may increase reinjury risk in patients who wish to return to competitive sport. 40 Objective assessment of aberrant neuromuscular strategies (asymmetry in measures of functional performance, strength, flexibility, and/or postural stability) that potentially lead to abnormal loading of the lower extremity, especially during high-risk single-limb maneuvers such as those used in the current investigation, could establish a foundation for efficacious RTS rehabilitation programs for young athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Motor control research in people with ACL rupture has explored the role of muscle activity in supporting joint stability and preventing re‐injuries (Table ) . Consequently, novel methods of optimizing muscle activation have been developed and refined within human physical therapy practices . Although not reported as a specific contributing factor to CCL disease within the veterinary literature, aberrant motor control is thought to adversely affect joint stability, stifle kinematics and joint loading .…”
Section: Comparison Of Motor Control Literature In Human and Canine Cmentioning
confidence: 99%
“…A deeper understanding of the interactions between mechanoreceptors, motor control and muscle activation would provide unique insights into the management of CCL injury, joint instability and initiation and progression of OA in affected dogs. Specific human neuromuscular rehabilitation interventions such as balance, functional training (i.e., performance‐based outcome measures, such as hopping or shuttle runs), perturbation training (i.e., unconscious reaction to a sudden movement), agility, and plyometric exercises (i.e., explosive and fast movements) have been developed and are currently being used to optimize dynamic stability . Similar neuromuscular retraining programs could also be developed to optimize specific aspects of dynamic stifle stability in dogs.…”
Section: Comparison Of Motor Control Literature In Human and Canine Cmentioning
confidence: 99%
See 1 more Smart Citation